The Effects of Bone Marrow Stromal Cells Therapy on the Improvement of Epilepsy Model in Rat Induced by pilocarpine - Ali Reza Abdani-Pour; Taghi Tarihi; Seyyed Javad Mirnajafi-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Temporal lobe epilepsy is the most common type of epilepsy in adult humans, which is characterized clinically by a progressive development of spontaneous recurrent seizures of temporal lobe origin. Because of the side effects of current treatment protocols, the resistance to pharmacological therapy in this investigation, bone marrow stromal cells were used to evaluate the recovery of epileptic rats induced by pilocarpine. Materials & Methods: In this randomized experimental research, the rats were divided into five groups, controls (untreated), three treated groups (12, 24 and 36 hours) and a group treated with the vehicle only. The animals in chronic phase were monitored via video monitoring system for three weeks (day & night). For assessment of the response for the treatment of epileptic's rat using BMSCs therapy, Racine scale was used as a behavioral test. BMSCs (2 - 3 million cells) were labeled with BrdU and were injected via tail vein rat 12, 24, 36 hours after first seizure. After 6 week all rats sacrificed and processed for paraffin, sectioned and for Cresyl violet staining. Data were analyzed by use of Wilcoxon signed Ranks test and Tukey's test. Results: The result of the study showed that the behavioral test in three week as follows: in control group (untreated), number of seizure is 6.25±1.3 in vehicle group, number of seizure was 6.2±0.8 the group which received BMSCs 12 h after seizure all rats died the group which received BMSCs (24 h after seizure), the number was 2±0.4 and the group which received BMSCs (36 h after seizure), the number of seizure was 2.25±0.47. There was significant difference between treated (2 and 36 hours) groups and other groups in number of seizure (P<0/01). Also, cells number was different significantly between same groups (P<0/01). Conclusion: Intravenous injection of BMSCs can improve number of attacks in epileptic's rats. Also, BMSCs injection can prevent from decrease of cells numerical density and degenerative damage.